Landscape attributes and first layer actual soil volume - Rao D V K N; Lakshmanan R; Vijayakumaran Nair P (Journal of the Indian Society of Soil Science, 2011)
Available literature shows that rubber (Hevea brasiliensis) is a surface feeder and 55-60;of fine roots are accommodated within top 10 cm depth of soil and more than 80;within top 30 cm depth. Because of this the impact of the first layer effective soil volume (FLESV) on growth and yield is conspicuously significant. However, FLESV cannot be taken as a constant because it can vary with pore space. Hence, it is necessary to understand variability in the first layer actual soil volume (FLASV) in a given landscape. Eleven soil samples collected from first mineral layer exposed at top, middle and bottom slope positions on different hills in a research farm growing rubber were characterized. Analysis revealed that slope class significantly influenced some physical properties like FLASV (p = 0.026, adjusted R2 = 0.496), sand (p=0.002, adjusted R2 = 0.744), clay (p = 0.002. adjusted R 2 = 0.732). Slope class also influenced some chemical properties like CEC (p = 0.045, adjusted R2 = 0.424) and exchangeable potassium (p = 0.023, adjusted R2 = 0.512) indicating the role of slope. Similarly, the regression of FLASV on slope and first layer thickness (FLT) was significant in and equation FLASV = 0.077-1.081**slope + 0.959**FLT - 0.149FLCF which was good (p = 0.007) that described 72;of variability in FLASV. Although another landscape attribute, elevation was included in the model it did not describe variability in significant terms. The cross section of slope along diffeernt directions passing through a single point indicated that probable inclusion of other landscape attributes like relief, profile curvature, slope length, specific catchment area, specific dispersal area may add more to the understanding of the geographical landscape and resultant soil properties in further studies.
Keywords: First layer actual soil volume; First layer coarse fragments; First layer effective soil volume; First layer thickness; Landscape attributes; Slope